Down Town Center a subterranean shopping center in Quezon Memorial Circle - Ramirez-Lam, Kyle Matthew Laurence D.; Sicam, Olivia Alma G. (Quezon City College of Architecture, University of the Philippines Diliman, 2023)
Quezon Memorial Circle is a valuable park at the heart of Quezon City. It houses the Quezon Memorial Shrine, the most iconic symbol of the city, as well as other recreational facilities for parkgoers to enjoy. The national park also serves as the primary node for Metro Manila's "Green Lung'. To further improve the facilities of Quezon Memorial Circle, the Quezon City Government initiated a redevelopment plan for the national park. One of the planned development projects, a shopping center, poses difficulty in design as it cannot be constructed in such a way that it will reduce the national park's green open spaces or disrupt the visual corridors toward the Shrine. Aa a solution, this comprehensive design project aims to design a subterranean shopping center, utilizing underground space to preserve green open spaces and the Shrine's value. Producing a shopping center in Quezon Memorial Circle also provides spaces for micro, small, and medium enterprises, advancing the city government's agenda of supporting local business. The project is undertaken with a proper review of related literature and precedents, site analysis, user behavior analysis, spatial analysis, and design proposal. The final design proposal utilized Quezon Memorial Circle's landscape patterns and subterranean architecture to create strategies in designing within the building height limit, expanding green open space, relating and distinguishing the shopping center from the park and shrine, and promoting micro, small, and medium enterprises.
include appendices.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Open spaces -- Quezon City; Quezon Memorial Circle; Shopping centers -- Quezon City; Underground areas -- Quezon City